Identification of Chemosensory Genes, Including Candidate Pheromone Receptors, in Phauda flammans (Walker) (Lepidoptera: Phaudidae) Through Transcriptomic Analyses - Hu, Jin; Wang, Xiao-Yun; Tan, Liu-Su; Lu, Wen; Zheng, Xia-Lin (Frontiers in Physiology, 2022)
The olfactory and gustatory systems play an irreplaceable role in all cycles of growth of insects, like host location, mating, and oviposition. Extensive chemosensory genes have been identified in many nocturnal moths via omics technology, while little is known about diurnal moths. As a member of diurnal moths, 2 sex pheromone components and 3 host plant volatiles that are attractive to adults of Phauda flammans were reported in our earlier studies. In order to further explore the process of sex pheromone and host plant volatiles recognition in P. flammans. The antennal full-length transcriptome sequence of P. flammans was obtained using Pacbio sequencing. Transcriptome analysis has found that total 180 candidate olfactory and gustatory genes including 58 odorant-binding proteins, 19 chemosensory proteins, 59 olfactory receptors, 28 ionotropic receptors, 14 gustatory receptors, and 2 sensory neuron membrane proteins were identified. Subsequently, the phylogenetic tree was established by both P. flammans and other lepidopteran species to investigate the orthologs. Among all the 7 candidate pheromone receptors genes PflaOR27, PflaOR41, PflaOR44, PflaOR49, and PflaOR51 were significantly highly expressed in the antennae than other non-antennae tissues. Sex-biased in antennae were also detected, PflaOR27, PflaOR29, and PflaOR44 showed higher expression in the male, whereas PflaOR49 revealed a female-biased expression. The functions of related ORs genes were also discussed. This research is not only filled the gap of olfactory and gustatory genes of P. flammans, but also provide basic data for future functional molecular mechanisms studies underlying P. flammans olfaction.